2014
DOI: 10.1007/s13762-014-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights into polyaromatic hydrocarbon biodegradation by Pseudomonas stutzeri CECT 930: operation at bioreactor scale and metabolic pathways

Abstract: Contamination of the environment with polycyclic aromatic hydrocarbons is one of the major problems facing the industrialized nations today. In this work, Pseudomonas stutzeri CET 930 was studied for the first time as bioremediation agent for the degradation of effluents containing phenanthrene, pyrene and benzanthracene, both individually and mixed. The promising results of degradation obtained at flask scale (92, 63 and 94 % in 7 days, respectively) marks the onset of the operation at bench scale bioreactor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This was attributed to the possibility that the microorganisms had utilised all the contaminants (serving as carbon sources) and hence, stopped replicating abundantly. Apart from substrate depletion, another plausible explanation for the drastic decline in microbial numbers is that toxic intermediates and by-products such as salicylate as well as oxy-PAHs; including PAH-ketones, quinones and coumarins 32 , 33 , 34 , 35 might have been produced and accumulated in the reactors thereby causing the death of the bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…This was attributed to the possibility that the microorganisms had utilised all the contaminants (serving as carbon sources) and hence, stopped replicating abundantly. Apart from substrate depletion, another plausible explanation for the drastic decline in microbial numbers is that toxic intermediates and by-products such as salicylate as well as oxy-PAHs; including PAH-ketones, quinones and coumarins 32 , 33 , 34 , 35 might have been produced and accumulated in the reactors thereby causing the death of the bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggested that the PAHs degradation route by strain BUK BTEG1 followed a similar course to that described for Pseudomonas sp. strain Jpyr-1 and strain CECT 930 (Moscoso et al, 2015) Pseudomonas otitidis strain P4 (Singh and Tiwary, 2016) and Pseudomonas stutzeri P2 (Singh and Tiwary, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that P . stutzeri has the capacity to degrade phenanthrene, pyrene and benzo(a)anthracene in a bioreactor with 95,78 and 82% of removal, respectively [28]. The studies mentioned above show that P .…”
Section: Resultsmentioning
confidence: 99%